2017
DOI: 10.3389/fpls.2017.01423
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a Chimeric Gene Encoding Insecticidal Crystal Protein Cry1Aabc of Bacillus thuringiensis in Chickpea (Cicer arietinum L.) Confers Resistance to Gram Pod Borer (Helicoverpa armigera Hubner.)

Abstract: Domain swapping and generation of chimeric insecticidal crystal protein is an emerging area of insect pest management. The lepidopteran insect pest, gram pod borer (Helicoverpa armigera H.) wreaks havoc to chickpea crop affecting production. Lepidopteran insects were reported to be controlled by Bt (cryI) genes. We designed a plant codon optimized chimeric Bt gene (cry1Aabc) using three domains from three different cry1A genes (domains I, II, and III from cry1Aa, cry1Ab, and cry1Ac, respectively) and expressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 53 publications
1
26
0
1
Order By: Relevance
“…However, it is important to subsequently test promising protein variants in a plant system. A recent example of this was performed by Das et al (2017). The authors found that feeding chickpea (Cicer arietinum) leaves expressing the Cry1Aabc protein, which had been generated by chimeragenesis, to larvae of the gram pod borer (Helicoverpa armigera Hubner) led to significantly increased mortality when compared to control leaves not expressing the protein.…”
Section: Engineering Of Bacterial Toxins and Their Applications In Plmentioning
confidence: 99%
“…However, it is important to subsequently test promising protein variants in a plant system. A recent example of this was performed by Das et al (2017). The authors found that feeding chickpea (Cicer arietinum) leaves expressing the Cry1Aabc protein, which had been generated by chimeragenesis, to larvae of the gram pod borer (Helicoverpa armigera Hubner) led to significantly increased mortality when compared to control leaves not expressing the protein.…”
Section: Engineering Of Bacterial Toxins and Their Applications In Plmentioning
confidence: 99%
“…Alternatively the constitutive promoter deployed in a particular crop species may either completely fail or demonstrate low levels of expression in the desired tissue/ organ leading to ineffective levels of intended phenotype. For instance, deployment of CaMV35S promoter for expression of Cry protein in chickpea revealed low expression levels in post-flowering stage (116 DAS) compared to that of pre-flowering stage (88 DAS) (Das et al, 2017). To this end, usage of tissue specific or inducible promoters that function in post-flowering stages and more specifically during pod development can overcome such a bottleneck.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional breeding approaches for insect resistance have limited success in chickpea due to lack of sufficient resistance source and incompatibility with many of the wild relatives 5 . Success of Bt-cotton in India led extensive research on developing transgenic crops especially, insect resistance Bt-chickpea [6][7][8][9][10][11][12] . Site of insertion of transgene in plant genome is critical as it could alter plant metabolism and toxicity of Bt-protein [13][14][15][16] .…”
mentioning
confidence: 99%
“…Site of insertion of transgene in plant genome is critical as it could alter plant metabolism and toxicity of Bt-protein [13][14][15][16] . Similarly, insertion of the transgene in active coding region of genome might be responsible for hemizygous state of some Bt-chickpea events with distorted segregation ratio 12 . Altered plant metabolism of genetically modified (GM) plants along with constitutive expression of chimeric Bt-transgenes and neomycin phospho-transferase II (nptII) can also influence the diversity, and richness of endophytic bacterial community that are often described as an important modulating agent of plants' fitness to adapt against environmental stresses.…”
mentioning
confidence: 99%